Makna Simbolik Tradisi MAPPACCI - Winda, Nur Hikmah; Suyuti, Nasruddin; Purwitasari, Paramitha (CV. ITTC INDONESIA, 2024)
This study investigates the symbolic meaning of tradition and tries to explain the Mappacci symbols of Bugis Traditional weddings in Pomburea Village, East Kolaka Regency, Lambandia District. The employed qualitative descriptive research methodology in this research is Charles Sanders Pierce's semiotic analysis. The research data comes from the symbols used in the Bugis Traditional Mappacci wedding procession from the Pomburea Village community. This study shows that mapacci is used in three main stages: Mapacci, Barasanji, and Khamatal Al-Qur'an. 2) The Mappacci ceremony, which is interpreted as